2010
DOI: 10.1203/00006450-201011001-01216
|View full text |Cite
|
Sign up to set email alerts
|

1216 Growth of Infants Fed with Nan is in Good Agreement with the Who Growth Standard: A Meta-Analysis

Abstract: Posters 602 n=6). Laser treatment was offered at a gestational age of 21 (17-26) weeks and delivery occurred at 29 (19-41) weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Mean values for all growth measures through age four months were within 0.5 SD of the median value. 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean values for all growth measures through age four months were within 0.5 SD of the median value. 27…”
Section: Resultsmentioning
confidence: 99%
“…Mean values for all growth measures through age four months were within 0.5 SD of the median value. 27 Serious adverse events. Serious adverse events reported throughout the study were ,5% in all groups (3.9%, 1.3%, and 2.3% for low-dose, regular-dose, and BF groups, respectively).…”
Section: Diarrheamentioning
confidence: 99%
“…Reducing the amount of protein in infant formulas could be one way to prevent excessive growth and minimize weight gain during childhood [ 89 102 ]. A meta-analysis of five randomized control trials showed that a diet of optimum quality and quantity protein formula leads to a growth pattern very close to the WHO growth standard at 4 months of age [ 103 ]. As well as increasing the risk of obesity, poor childhood nutrition and defective metabolic programming, have also been shown to trigger other NCDs, such as type 2 diabetes, hypertension, and cardiovascular disease, in later life [ 50 104 105 106 ].…”
Section: Discussionmentioning
confidence: 99%